Depicting Migrants’ Life in Moroccan Newspapers - Dib, Salim (International Journal of Language and Literary Studies, 2023)
Sub-Saharan migrants in Morocco have become a part and partial issue in Moroccan newspapers as their number has enormously risen. Media, in general, brings to the public most of the images, data, and facts about migrants. For this reason, the media’s treatment of migration generates currents of opinion and attitudes towards these people. Furthermore, since it has been massively highlighted in Moroccan newspapers, many people would interpret migration from Sub-Saharan countries primarily from the messages from the Media. Therefore, the readers’ images would be influenced by how the issue is depicted and portrayed in newspapers. This article aims to shed light on the way Moroccan newspapers deal with the issue of migration towards Morocco from Sub-Saharan countries and how their life was depicted after the launch of the new migration policy. With these objectives in mind, this study is based on qualitative data collection of news items and reports from four daily printed newspapers in Morocco. Relying on Content analysis has demonstrated a stereotypical misrepresentation and a slight change in topics coverage of ’black’ African migrants in news narratives.